Toll-like Receptor 4 Engagement on Dendritic Cells Restrains Phago-Lysosome Fusion and Promotes Cross-Presentation of Antigens - Alloatti, Andrés (2015)
The initiation of cytotoxic immune responses by dendritic cells (DCs) requires the presentation of antigenic peptides derived from phagocytosed microbes and infected or dead cells to CD8(+) T cells, a process called cross-presentation. Antigen cross-presentation by non-activated DCs, however, is not sufficient for the effective induction of immune responses. Additionally, DCs need to be activated through innate receptors, like Toll-like receptors (TLRs). During DC maturation, cross-presentation efficiency is first upregulated and then turned off. Here we show that during this transient phase of enhanced cross-presentation, phago-lysosome fusion was blocked by the topological re-organization of lysosomes into perinuclear clusters. LPS-induced lysosomal clustering, inhibition of phago-lysosome fusion and enhanced cross-presentation, all required expression of the GTPase Rab34. We conclude that TLR4 engagement induces a Rab34-dependent re-organization of lysosomal distribution that delays antigen degradation to transiently enhance cross-presentation, thereby optimizing the priming of CD8(+) T cell responses against pathogens.